2014
DOI: 10.15201/hungeobull.63.3.3
|View full text |Cite
|
Sign up to set email alerts
|

In the middle of nowhere: Gated neighbourhoods in Vilnius region as a new lifestyle?

Abstract: This article provides an overview about the new tendencies on the Lithuanian housing market shedding light on the development of the gated and guarded neighbourhoods (GGNs). Field surveys and interviews with developers, residents as well as local planning authorities in Vilnius and its surroundings provide the basis of discussion about the "fencing phenomenon". Can this phenomenon be explained by such factors like socio-economic segregation in the city, extensive marketing or a specifi c niche on the market? T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Vienas tokių pavyzdžių yra Lietuvos socialinių geografų pastangos aprašyti gyvenimo uždarose ir saugomose vietovėse patirtis (Krupickaitė ir kt. 2011;Krupickaitė et al 2014;PociūtėSereikienė ir Krupickaitė 2016). Kitaip nei anksčiau aprašytuose socialinių geografų darbuose, čia neapsiribojama vien tik paprastu miesto vietovių žemėlapiavimu, kal bama apie pasirinkimo gyventi tokiuose rajonuose motyvaciją, pateikiami gyvenimo tokiuose būstuose patirties vertinimai.…”
Section: Kas Gi Išminko Materialias Ir Simbolines Vilniaus Miesto Forunclassified
“…Vienas tokių pavyzdžių yra Lietuvos socialinių geografų pastangos aprašyti gyvenimo uždarose ir saugomose vietovėse patirtis (Krupickaitė ir kt. 2011;Krupickaitė et al 2014;PociūtėSereikienė ir Krupickaitė 2016). Kitaip nei anksčiau aprašytuose socialinių geografų darbuose, čia neapsiribojama vien tik paprastu miesto vietovių žemėlapiavimu, kal bama apie pasirinkimo gyventi tokiuose rajonuose motyvaciją, pateikiami gyvenimo tokiuose būstuose patirties vertinimai.…”
Section: Kas Gi Išminko Materialias Ir Simbolines Vilniaus Miesto Forunclassified
“…Part of this research was focused on GCs, which we distinguish as a residential or mixed-use house group with the following characteristics: 1) the land is fully fenced and the entrance is limited to cars and pedestrians and 2) the territory is under video surveillance or protected by security staff. Such settlements are privately managed and their residents are usually bound by contracts and commitments (Burneika et al, 2017;Krupickaitė et al, 2014;Pociūtė-Sereikienė, Krupickaitė, 2016).…”
Section: Perspectives Of Gated Communities' Integration In Post-sociamentioning
confidence: 99%
“…Most of new settlements built in suburbs are like welfare islands, in which the communities are quite active. A case study of the 'Neries kilpos' GC in a suburb of Vilnius (Krupickaitė et al, 2014) showed that the socio-demographic structure of it was quite homogeneous. The majority of the residents belong to the upper-middle class, most of them have a university degree, are employed or free-standing high-quality specialists, businessmen, medical doctors, etc.…”
Section: Perspectives Of Gated Communities' Integration In Post-sociamentioning
confidence: 99%